1999
DOI: 10.1021/ma990853f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Poly(propylene sulfide) Studied by Dynamic Mechanical Measurements and Dielectric Spectroscopy

Abstract: Dynamical properties of bulk poly(propylene sulfide) (PPS) were investigated for a range of molar masses between 600 and 50 000 g/mol. The primary and secondary relaxation (α-relaxation and β-relaxation) were studied using dielectric spectroscopy. The local segmental relaxation (α-relaxation) and the chain backbone conformational relaxation were studied using dynamic mechanical measurements. The dynamical properties of PPS are compared to those of poly(propylene oxide) (PPO) and are shown to be very similar. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 24 publications
(33 reference statements)
5
43
0
Order By: Relevance
“…As reported in previous studies,, the amorphous PPS0 exhibits a characteristic phase transition process, a rubber–glass state transition, and experiences a disorder–order transition process (cold crystallization) when heated from room temperature, as depicted in Fig. , which shows the DSC heating traces of PPS with various crystallinities obtained a heating rate of 3 °C min −1 .…”
Section: Resultssupporting
confidence: 61%
“…As reported in previous studies,, the amorphous PPS0 exhibits a characteristic phase transition process, a rubber–glass state transition, and experiences a disorder–order transition process (cold crystallization) when heated from room temperature, as depicted in Fig. , which shows the DSC heating traces of PPS with various crystallinities obtained a heating rate of 3 °C min −1 .…”
Section: Resultssupporting
confidence: 61%
“…In the low temperature range (from −100 to −30°C), one can observe the β II ‐relaxation, which can be ascribed to the phenyl ring flips like in PET. Nicol et al [45, 46] showed experimentally by introducing hydrogen bonding end‐groups in PPS that the energy of β‐relaxation is independent of molar masses and ascribed this process to the conformational changes of chain backbone. In the case of pure PPS which we studied, the maxima of ε″ related to the β II ‐relaxation are hardly seen for the lowest frequencies and activation energy of this process cannot be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Crystalline or glassy polysulfides may, therefore, present a slow (because of the slower dynamics of the material) or poorly reproducible (because of the dependency of the mobility on the thermal history of the sample, controlling the free volume or the extent of crystallinity) oxidation behaviour. PPS does not have these drawbacks, being completely amorphous with a very low T g ;169 as a result, the oxidation proceeds smoothly, with a surface mechanism in macroscopic materials (Figure 4) or a bulk one in nanoparticles 170. Furthermore, PPS can be oxidised under biomimetic conditions, that is, with oxidants typically encountered in a biological environment and, also, through the action of oxidising enzymes,171, 172; the relatively low proportion of the PPS aliphatic component (three carbon atoms per sulphur) makes its oxidation products completely water‐soluble already at the level of the oxidation to sulfoxides173.…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%